Storytelling, and its role in the consolidation of the values of faith, in the collection of “The Words” by BediuzzamanSaid Nursi - حسن سرباز (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Storytelling is among literary styles suitable for the expression of ideas and the dissemination of values and virtues, while having a charming power in stirring up emotions and feeding it. Therefore, a large portion of the pages of the Holy Quran and the Prophetic Hadiths includes this style, and Allah has ordered his Prophet (pbuh) to use it as a means of propagating the Islamic call and consolidating the doctrine of monotheism in the hearts of people and teaching themthe Islamic principles and humanistic values, and also as a means for contemplatingthe signs existing inthe world outside and inside us. The preachers and reformers, including BediuzzamanSaid Nursi, has benefited from the storytelling and considered it a great educational tool for propagating Islamic values and ideas, following the Quran and Sunnah. Bediuzzamanused this literary method in “Rasael al-Nur” Collection to bring the meanings closer to mind and show the reasonableness of Islamic truths. This research aims at studying the use of storytelling in the collection of "The Words" and its role in the consolidation of the values of faith, according to the descriptive-analytical methodology. The researcher has studied thirteen sample stories which could be called short stories. These stories were used to interpret the Quranic verses and to clarify the concepts of faith and themoral values. The stories contained in “The Words” are dramatic narratives considered by Bediuzzamanto becertainly true. In the majority of Bediuzzaman’s dramatic narratives, there is an introduction inviting the addressee to listen to his story so that they can understand the subject, even he sometimes addresses and invites himself to listen to the current story. Bediuzzaman doesn’t leave his audience to deduce lessons from the stories by themselves, but explains the story and his intention behindit after finishing telling it.